ENVIRONMENTAL AND PATHOGENETIC BASES OF FUNCTIONING OF PARASITIC SYSTEM FORMED BY TRICHINELLA (TRICHINELLA RAILLIET, 1895) - V. P. Tolokonnikov; G. M. Mukhtarova (Юг России: экология, развитие)
Aim. The aim is to study the environmental and pathogenetic bases for the functioning of the system formed by the parasite Trichinella (Trichinella Railliet, 1895) in the Southern and North Caucasian Federal District of the Russian Federation.Methods used. We used comparative and historical, comparative and geographical methods, epizootic survey, statistical processing and data analysis. To detect and identify Trichinella we used microscopic and biochemical methods, as well as the methods of enzyme immunoassay (ELISA) and polymerase chain reaction (PCR).Results. We present the data on the spread of trichinosis, environmental pathogens, ways and factors contributing to the infection of humans and animals that are susceptible to the parasite. We also note epidemiological, epizootic, social and economic significance of this disease.Conclusions. We analyzed the relationship of environmental and pathogenetic factors determining the functioning features of the system formed by the Trichinella parasite. We also attempted to explain the results that can be used to improve programs for prevention and control of zoonoses.